2006
DOI: 10.1111/j.1365-2990.2006.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral calpain in fatal falciparum malaria

Abstract: Disruption of axonal transport may represent a final common pathway leading to neurological dysfunction in cerebral malaria (CM). Calpains are calcium (Ca2+)-activated cysteine proteases which have been implicated in axonal injury in neurological diseases of various aetiologies. In this study we examined the association between mu- and m-calpain, the specific inhibitor calpastatin, and axonal injury in post mortem brain tissue from patients who died from severe malaria. Calpains were associated with axons labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…The proposed mechanism suggests that Epo could increase axonal calcium levels as it has been shown to activate neural voltage-gated calcium channels [46]. Axonal injury in severe malaria is likely to involve increased levels of intracellular calcium reflected by increased levels of the calcium-activated cysteine protease, calpain [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism suggests that Epo could increase axonal calcium levels as it has been shown to activate neural voltage-gated calcium channels [46]. Axonal injury in severe malaria is likely to involve increased levels of intracellular calcium reflected by increased levels of the calcium-activated cysteine protease, calpain [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes also have been implicated in neuronal death in neurological diseases (11,17,60), including CM (33,56). A number of protease inhibitors were expressed on the arrays, including CTLA-2␣ (22), and may represent a host mechanism to limit the damage mediated by proteases, particularly since these proteolytic processes can lead to development of intracerebral hemorrhaging (63), which is an invariable finding in human and murine CM.…”
Section: Discussionmentioning
confidence: 99%
“…Increased calpain levels have previously been reported in human and murine CM (45, 46). We corroborate these findings as we also found this when blotting for two independent markers of calpain activity: p25 and a 150 kDa fragment of α-spectrin.…”
Section: Discussionmentioning
confidence: 69%
“…We corroborate these findings as we also found this when blotting for two independent markers of calpain activity: p25 and a 150 kDa fragment of α-spectrin. Thus, aberrant VEGF signaling may activate calpains causing endothelial pathology and neuropathology (38, 45). We found that EPO therapy reduces cerebral VEGF and markers associated with calpain activity to levels comparable with uninfected mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation